2014
DOI: 10.1021/jm4015422
|View full text |Cite
|
Sign up to set email alerts
|

Nucleotide Prodrugs of 2′-Deoxy-2′-spirooxetane Ribonucleosides as Novel Inhibitors of the HCV NS5B Polymerase

Abstract: The limited efficacy, in particular against the genotype 1 virus, as well as the variety of side effects associated with the current therapy for hepatitis C virus (HCV) infection necessitates more efficacious drugs. We found that phosphoramidate prodrugs of 2'-deoxy-2'-spirooxetane ribonucleosides form a novel class of HCV NS5B RNA-dependent RNA polymerase inhibitors, displaying EC50 values ranging from 0.2 to >98 μM, measured in the Huh7-replicon cell line, with no apparent cytotoxicity (CC50 > 98.4 μM). Conf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(28 citation statements)
references
References 35 publications
1
27
0
Order By: Relevance
“…15,16 They were complemented with the spirocyclic 2'-deoxy-2'-spirocyclopropyl and the 2'-deoxy-2'-spirooxetane moeity. 17,18,19 Recently, the 2'-α-fluoro-2'-β-chloro derivative was also reported 20 ( Figure 1). These 2'-variants not only need to mimic the interaction between the polymerase and the 2'-α-OH group present in natural ribonucleotides, they also must conform to the steric limitations of the corresponding 2'-region of the polymerase to result in proper inhibition thereof.…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…15,16 They were complemented with the spirocyclic 2'-deoxy-2'-spirocyclopropyl and the 2'-deoxy-2'-spirooxetane moeity. 17,18,19 Recently, the 2'-α-fluoro-2'-β-chloro derivative was also reported 20 ( Figure 1). These 2'-variants not only need to mimic the interaction between the polymerase and the 2'-α-OH group present in natural ribonucleotides, they also must conform to the steric limitations of the corresponding 2'-region of the polymerase to result in proper inhibition thereof.…”
Section: Introductionmentioning
confidence: 91%
“…22 A few examples of anti-HCV active phosphoramidates are depicted in Figure 2. 18,20,23,24 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 The most successful example of this approach is 1, which is the R P diastereomer of a phosphoramidate prodrug of 2'-deoxy-2'α-fluoro-2'-β-C-methyl uridine. The use of 1 was first approved by the FDA for triple therapy in combination with interferon/ribavirin for treatment of HCV patients infected with genotypes 1 and 4, and in combination with ribavirin alone for patients infected with HCV genotypes 2 and 3 in 2013.…”
Section: Introductionmentioning
confidence: 99%
“…Jonckers et al identified a series of phosphoramidate prodrugs of 2'-deoxy-2'-spirooxetane ribonucleosides. These prodrugs showed antiviral activity in HCV replicon assay (Huh-7 cells) with an EC50 value ranging from 0.2 to>98 μM, but failed to show potency in cytotoxicity assay [41].…”
Section: Pyrimidine Nucleoside Inhibitorsmentioning
confidence: 99%
“…63 A unique series of 1 0 -substituted C-nucleosides possessing a 4-aza-7,9dideaza-adenosine base 56 were shown to have modest activity against HCV with improved potency upon preparation of their S-acyl-2-thioethyl prodrugs 57. [67][68][69][70] In the 2 0 -cyclopropyl series, TMC647078 (59) was active in the replicon assay (EC 50 ¼ 7.3 μM) across all GTs, but exhibited reduced activity against NS5B S282T. Preparation of the 2 0 -C-methyl-1 0 -cyano derivatives eliminated the cytotoxicity and subsequent development of the 5 0 -phosphoramidate prodrug of the 1 0 -cyano analog resulted in the clinical candidate GS-6620 58.…”
Section: Hepatitis C Virusmentioning
confidence: 99%
“…7-Heterocyclic substituted 7-deaza-adenine derivatives containing either the 2 0 -F-2 0 -C-methyl or 2 0 -OH-2 0 -C-methyl substitution (65,66) demonstrated modest HCV replicon potency and modest liver triphosphate levels when administered in vivo to rats. 71 In a similar fashion, an extensive series of 6-substituted-7-heteroaryl-7-deazapurine ribonucleosides (68)(69)(70) were studied, but replicon activity was generally correlated with cytotoxicity. 71 In a similar fashion, an extensive series of 6-substituted-7-heteroaryl-7-deazapurine ribonucleosides (68)(69)(70) were studied, but replicon activity was generally correlated with cytotoxicity.…”
Section: Hepatitis C Virusmentioning
confidence: 99%